2012
DOI: 10.1016/j.mayocp.2012.06.021
|View full text |Cite
|
Sign up to set email alerts
|

HIV Screening in the Health Care Setting: Status, Barriers, and Potential Solutions

Abstract: Thirty years into the human immunodeficiency virus (HIV) epidemic in the United States, an estimated 50,000 persons become infected each year: highest rates are in black and Hispanic populations and in men who have sex with men. Testing for HIV has become more widespread over time, with the highest rates of HIV testing in populations most affected by HIV. However, approximately 55% of adults in the United States have never received an HIV test. Because of the individual and community benefits of treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 38 publications
3
38
1
2
Order By: Relevance
“…Our findings are consistent with previously reported data which demonstrate increased testing specifically among Blacks. 7,8,23 However, contrary to national trends showing stable HIV testing, 4,24 we found that testing increased in Pennsylvania. Similarly, HIV testing rose in Washington DC, which, like Pennsylvania, received financial and structural support from the CDC-led Expanded Testing Initiative.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Our findings are consistent with previously reported data which demonstrate increased testing specifically among Blacks. 7,8,23 However, contrary to national trends showing stable HIV testing, 4,24 we found that testing increased in Pennsylvania. Similarly, HIV testing rose in Washington DC, which, like Pennsylvania, received financial and structural support from the CDC-led Expanded Testing Initiative.…”
Section: Discussioncontrasting
confidence: 73%
“…[30][31][32] Factors that could have slowed adherence to the CDC recommendations during the study time period include the persistence of policies at the state and health institution level in favor of a separate written informed consent for HIV testing, the lack of awareness of the CDC recommendations among physicians and patients, 24 the stigma associated with HIV testing, 33,34 and challenges with financial reimbursement for opt-out testing. 24 Pennsylvania only removed the provision for written informed consent for HIV testing in 2011, 5 a year after completion of our last survey wave. Old data indicate that states where consent procedures were either streamlined or eliminated saw increases in HIV testing compared to states where written informed-consent statutes were enforced.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrate that significant barriers to implementation of universal HIV testing in healthcare settings still exist. One of those barriers may be connected to the insecurity that healthcare professionals may feel while discussing the topic of HIV testing with their patients, particularly those from low-risk backgrounds, citing that discussing HIV testing would be uncomfortable for the patient and might damage the patient–physician relationship 26. In our study, we found that the two most common barriers to send or offer an HIV test were under-recognition of the patients as belonging to a risk group mainly by primary care physicians and not thinking on HIV at all, which was more common among specialists.…”
Section: Discussionmentioning
confidence: 99%
“…The incorrect assumptions concerning routine HIV testing and the false reassurance might influence patients' decisions not to undergo appropriate screening, disclose high-risk behavior, or seek appropriate testing for sexually transmitted diseases in the future [18,19]. These factors have potentially important implications and could conceivably contribute to late diagnosis of HIV, delayed initiation of ART and preventive care for HIV-infected individuals, continued risky behavior, and onward transmission of infection [6,20]. Other potential consequences of patients' misperceptions regarding routine HIV testing include unintentionally misinforming healthcare providers about previous HIV tests and providing inaccurate self-report when surveyed for surveillance estimates [20].…”
Section: Discussionmentioning
confidence: 99%
“…Identified provider-related barriers include lack of familiarity with current HIV screening guidelines, uncertainty about consent recommendations, and concerns about patients' perception and refusal [5,6]. In fact, despite recommendations for universal HIV screening, risk-based screening persists and screening rates remain unsatisfactory [7].…”
Section: Introductionmentioning
confidence: 99%